A Motivational Theory of Charismatic Leadership: Envisioning, Empathy, and Empowerment - CHOI, Jaepil (Institutional Knowledge at Singapore Management University, 2009)
The motivational effects of charismatic leadership are examined in greater detail. Charismatic leadership is assumed to have three core components: envisioning, empathy, and empowerment. A charismatic leader's envisioning behavior influences followers' need for achievement, and the leader's empathic behavior stimulates followers' need for affiliation. Followers' need for power is enhanced by a charismatic leader's empowerment practices. It is further suggested that the behaviors of a charismatic leader and the enhanced followers' needs promote clearer role perceptions, improved task performance, greater job satisfaction, stronger collective identity and group cohesiveness, more organizational citizenship behaviors, and stronger self-leadership among the followers. The contextual factors which may influence the motivational effects of charismatic leadership are also discussed